3(s+4(s+12))=

Simple and best practice solution for 3(s+4(s+12))= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(s+4(s+12))= equation:


Simplifying
3(s + 4(s + 12)) = 0

Reorder the terms:
3(s + 4(12 + s)) = 0
3(s + (12 * 4 + s * 4)) = 0
3(s + (48 + 4s)) = 0

Reorder the terms:
3(48 + s + 4s) = 0

Combine like terms: s + 4s = 5s
3(48 + 5s) = 0
(48 * 3 + 5s * 3) = 0
(144 + 15s) = 0

Solving
144 + 15s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-144' to each side of the equation.
144 + -144 + 15s = 0 + -144

Combine like terms: 144 + -144 = 0
0 + 15s = 0 + -144
15s = 0 + -144

Combine like terms: 0 + -144 = -144
15s = -144

Divide each side by '15'.
s = -9.6

Simplifying
s = -9.6

See similar equations:

| 28x^2+28x+7=0 | | 6x-28y=-10 | | 4.2y-2y=16.8 | | 6x-28=-10 | | 2(-2-2m)=-4-3m | | 7-3(4x+2)=6(2x+3)17 | | X+2=2(3x-8) | | 14+19+x*3=17 | | 4a^3+6a^2+5a=0 | | 1+x=10-2x | | -6x-15=58 | | ax+b+cx=d | | 2x^2-4=60 | | x^2+2x(0.4)=0.84 | | -x+2y+4z=-11 | | f(x)=x^2+13x+37 | | B=pn+pforn | | 12x+2=(7)2x-3 | | 6p^2+25x+4=0 | | y=.33(x-27) | | 2.75f=24.5 | | 5-6lnx=20 | | (3x-c)(x-3)=12 | | 5n^2=-5n+160 | | 7s+8l=180 | | 4x-2=3(2x+5)-31 | | 5x-20=2x | | x+8y=29 | | 2t^3+13t+15t=0 | | y=9x^2+x+7 | | 4(8x+10)=32x-8 | | 9k+27=0 |

Equations solver categories